NAVMETRO®: PRELIMINARY STUDY APPLICATIONS OF USABILITY ASSESSMENT METHODS - Ferreira, Eveline Januário (Human Factors in Design, 2013)
<!– /* Font Definitions */ @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:3 0 0 0 1 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; p.Abstract, li.Abstract, div.Abstract mso-style-name:Abstract; margin-top:0cm; margin-right:0cm; margin-bottom:4.0pt; margin-left:0cm; text-align:justify; mso-pagination:widow-orphan; font-size:10.0pt; mso-bidi-font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> NAVMETRO® is a spoken dialogue system that provides information and a guidance function to the people with visual disabilities on Trindade’s metro station, in Porto, Portugal. The system usability in addition to assure the quality dialogue for all costumers should ensure the success in the guidance on the desirable way in the metro station. This article presents the results of the preliminary assessment developed on NAVMETRO® and that represents an important stage of the usability assessment of this system.